Laparoscopic-assisted Peritoneal Shunt Insertion for Ventriculoperitoneal and Lumboperitoneal Shunt Placement. Issue 3 (June 2015) - Sosin, Michael; Sofat, Sujata; Felbaum, Daniel R.; Seastedt, Kenneth P.; McGrail, Kevin M.; Bhanot, Parag
<x xml:space="preserve">Abstract</x> Purpose: The purpose of this study was to describe operative times, complication rates, and outcomes following laparoscopic placement of the peritoneal catheter in ventriculoperitoneal (VP) and lumboperitoneal (LP) shunt insertion. Methods: A retrospective review was performed of those who underwent laparoscopic-assisted VP or LP shunt insertion from July 2007 to August 2011. Results: The study included 53 consecutive patients (35 women and 18 men). Mean age was 51 years (range, 16 to 83 y), mean BMI was 27.6 (range, 16 to 54), and 35.8% of the patients had previous abdominal surgery. Mean operative time for VP shunt placement was 68.2±19.0 minutes, and for LP shunt placement 84±12.4 minutes. There were no intraoperative complications, and conversion to minilaparotomy was 0%. There were 2 distal catheter–associated complications. Conclusions: Laparoscopic-assisted VP/LP shunt placement is associated with a low incidence of distal catheter malfunction. Direct visualization of shunt placement into the peritoneal cavity is a major advantage making it a viable alternative over traditional techniques.